Social Status of Women as a Predictor of Nutritional Status among Pregnant Women in Dekina Local Government Area, Kogi State - Omachi, Sunday (International Journal of Human Kinetics, Health and Education, 2022)
The dietary intake of pregnant women needs to provide energy and nutrients for the mother as well as the foetus. However, social status or valuation affects caloric intake among pregnant women in developing countries. The purpose of this study was to investigate social status of women as a predictor of nutritional status among pregnant women in Dekina Local Government Area, Kogi State. A correlation research design was used to investigate 204 respondents drawn from Primary Health Centres in the twelve political wards in Dekina LGA. The respondents were sampled from the health facilities in those wards through purposive sampling technique. A close–ended questionnaire was used to obtain responses from the respondents. Data collected for this study were analyzed using mean scores, standard deviation and Pearson product moment correlation coefficient analysis at the 0.05 level of significance. Pearson’s correlation between means scores of social status of women (2.857) and nutritional status of pregnant women (2.966) showed r-value of 0.747 (critical value: 0.087) and a P-value of 0.000. The finding showed that social status of women is a significant predictor of nutritional status among pregnant women in Dekina Local Government Area, Kogi State. Based on the finding, it was recommended that socio-cultural practices that place greater valuation on certain household members over others should be abolished. This involves understanding and working within the deep structure of cultural settings.